Translocation of Exogenous FGF1 and FGF2 Protects the Cell against Apoptosis Independently of Receptor Activation. Issue 21 (19th October 2018) - Kostas, Michal; Lampart, Agata; Bober, Joanna; Wiedlocha, Antoni; Tomala, Justyna; Krowarsch, Daniel; Otlewski, Jacek; Zakrzewska, Malgorzata
Abstract: FGF1 and FGF2 bind to specific cell-surface tyrosine kinase receptors (FGFRs) and activate intracellular signaling that leads to proliferation, migration or differentiation of many cell types. Besides this classical mode of action, under stress conditions, FGF1 and FGF2 are translocated in a receptor-dependent manner via the endosomal membrane into the cytosol and nucleus of the cell. However, despite many years of research, the role of translocated FGF1 and FGF2 inside the cell remains unclear. Here, we reveal an anti-apoptotic activity of intracellular FGF1 and FGF2, which is independent of FGFR activation and downstream signaling. We observed an inhibition of cell apoptosis induced by serum starvation or staurosporine upon treatment with exogenous FGF1 or FGF2, despite the presence of highly potent FGFR inhibitors. Similar results were found when the tyrosine kinase of FGFR1 was completely blocked by a specific mutation. Moreover, the anti-apoptotic effect of the growth factors was abolished by known inhibitors of the translocation of FGF1 and FGF2 from the endosomes to the interior of the cell. Interestingly, FGF2 showed higher anti-apoptotic activity than FGF1. Since FGF2 is not phosphorylated by PKCδ and is present inside the nucleus longer than is FGF1, we speculated that the different activities could reflect their diverse nuclear export kinetics. Indeed, we observed that FGF1 mutations preventing binding to nucleolin and therefore phosphorylation in the nucleus affect the anti-apoptotic activity of FGF1. Taken together, our data indicate that the translocation of FGF1 and FGF2 protects cells against apoptosis and promotes cell survival. Graphical abstract: Highlights: Translocated FGF1 and FGF2 inhibit apoptosis in the presence of FGFR inhibitors. FGF1 and FGF2 exhibit anti-apoptotic activity in cells expressing inactive FGFR. Anti-apoptotic effect of FGF1 and FGF2 is abolished by inhibitors of translocation. Ectopic expression of FGF1 or FGF2 inhibits apoptosis. Translocation of FGF1 and FGF2 protects cells against apoptosis.